KAJIAN TEKNO-EKONOMI CARBON STORAGE DI INDONESIA - Prasojo, Hadi
CO2 is the main anthropogenic gas contributing to the greenhouse effect and global warming. Many processes or industrial activities contributing to climate change by emitting CO2: power plant, cement production, refineries, iron and steel industry, petrochemical industry, oil and gas processing, etc. Indonesia, with CO2 emissions also increased, it should undertake concrete measures to reduce GHG emissions in accordance with the announced target. One concrete step is the application of Carbon Capture and Storage (CCS) in Indonesia. In this study discussed how the potential storage capacity of Indonesia, particularly in oil and gas reservoirs. Also discussed a case study example fired power plant coal so note the estimated time for injection / storage emissions. Then, discuss the economic side of CCS projects, through the techno-economic discussion compression-pump, transport, and injection and storage of CO2. The main literature source of storage capacity calculation comes from the Carbon Sequestration Leadership Forum (CSLF), while the techno-economic comes from David L. McCollum. Based on the results of this study, a large potential theoritical storage capacity of carbon in oil and gas reservoirs in Indonesia in total amounted to 6,836.5 M tons of CO2. Meanwhile, a case study of emissions from coal power plants with a capacity of 2 x 1,000 MW can be injected at the East Java Basin during 16.14 year. The range cost of the injection and storage of CO2 in geological formations in Indonesia about 13.07 – 17.76 $/tonnes CO2 for compression and pumping, 2.52 – 44.15 $/tonnes CO2 for transportation, and 1.91 – 2.17 $/tonnes CO2 for injection and storage.